Reduced Serum Osteocalcin in High‐Risk Alcohol Using People Living With HIV Does Not Correlate With Systemic Oxidative Stress or Inflammation: Data From the New Orleans Alcohol Use in HIV Study. (1st October 2019) - Watt, James; Schuon, Jonathan; Davis, Jacob; Ferguson, Tekeda F.; Welsh, David A.; Molina, Patricia E.; Ronis, Martin J. J.
Abstract : Background: HIV infection is now largely a chronic condition as a result of the success of antiretroviral therapy. However, several comorbidities have emerged in people living with HIV (PLWH), including alcohol use disorders and musculoskeletal disorders. Alcohol use has been associated with lower bone mineral density, alterations to circulating bone turnover markers, and hypocalcemia. The pathophysiological basis of bone loss in the PLWH population is unclear but has been suggested to be linked to oxidative stress and inflammation. To test the hypothesis that PLWH consuming excessive alcohol have altered markers of bone turnover and/or calcium homeostasis in association with oxidative stress, we correlated measurements of alcohol consumption with markers of oxidative stress and inflammation, serum calcium concentrations, and measurements of bone turnover, including c‐terminal telopeptide cross‐links (CTX‐1) and osteocalcin. Methods: Data were drawn from cross‐sectional baseline data from the ongoing New Orleans Alcohol Use in HIV (NOAH) study, comprised of 365 in care PLWH. Alcohol consumption measures (Alcohol Use Disorders Test, 30‐day timeline follow‐back calendar, and phosphatidylethanol [PEth]) were measured in a subcohort of 40 subjects selected based on highest and lowest PEth measurements. Multivariate linear regression was performed to test the relationships between alcohol consumption and systemic oxidative stress (4‐hydroxynonenal; 4‐HNE) and inflammation (c‐reactive protein; CRP). Results: Serum calcium and CTX‐1 did not differ significantly between the high and low‐PEth groups. Individuals in the high‐PEth group had significantly lower serum osteocalcin (median low‐PEth group: 13.42 ng/ml, inter‐quartile range [IQR] 9.26 to 14.99 ng/ml; median high‐PEth group 7.39 ng/ml, IQR 5.02 to 11.25 ng/ml; p = 0.0005, Wilcoxon rank‐sum test). Osteocalcin negatively correlated with PEth (Spearman r = −0.45, p = 0.05) and self‐reported measures after adjusting for covariates. Alcohol consumption showed mild, but significant, positive associations with serum 4‐HNE, but not with CRP. Osteocalcin did not correlate with either 4‐HNE or CRP. Conclusions: In this subcohort of PLWH, we detected significant associations between at‐risk alcohol use and osteocalcin, and at‐risk alcohol use and serum 4‐HNE, suggesting suppression of bone formation independent of increased systemic oxidative stress with increasing alcohol consumption. Abstract : Alcohol use and HIV adversely impact bone health. In the New Orleans Alcohol Use in HIV (NOAH) study – an ongoing, longitudinal study of in care people living with HIV (PLWH) – participants with at‐risk alcohol consumption (quantified by phosphatidylethanol (PEth), AUDIT, and timeline followback) had significantly lower measures of the serum marker osteocalcin compared to low‐risk consumers, suggesting an imbalance in healthy bone turnover. Subsequent analyses highlight independent, adverse associations between alcohol consumption and both bone turnover and inflammation in PLWH.